Is Adult Attention-Deficit Hyperactivity Disorder Being Overdiagnosed?. (July 2015) - Paris, Joel; Bhat, Venkat; Thombs, Brett
This review offers a perspective on the question as to whether attention-deficit hyperactivity disorder (ADHD) is being overdiagnosed in adults. Considering underlying causes as well as consequences, we conclude that the diagnosis of adult ADHD should be made cautiously, making use of multiple sources of information, including self-report, clinical interviews, collateral information, childhood documentation, and neuropsychological testing. Routine screening with symptom checklists is insufficient, and stimulant response is diagnostically uninformative. The causes of overdiagnosis may include changes in diagnostic thresholds, poor diagnostic practices, and advertising by the pharmaceutical industry. Overdiagnosis leads to overtreatment, and dramatic increases in prescriptions for adult ADHD during the last decade should arouse concern.